2013
DOI: 10.1111/j.1365-3164.2012.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for pythiosis

Abstract: Background -Pythiosis is a life-threatening disease caused by Pythium insidiosum. Photodynamic therapy (PDT) is an alternative treatment to surgery that uses the interaction of a photosensitizer, light and molecular oxygen to cause cell death.Objectives -To evaluate the effect of PDT on the in vitro growth of P. insidiosum and in an in vivo model of pythiosis.Methods -For in vitro studies, two photosensitizers were evaluated: a haematoporphyrin derivative (Photogem â ) and a chlorine (Photodithazine â ). Ampho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“… 15 Pires et al reported that photodynamic therapy was effective both in vitro and in vivo in the inactivation of Pythium insidiosum , representing a new approach for treating pythiosis. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Pires et al reported that photodynamic therapy was effective both in vitro and in vivo in the inactivation of Pythium insidiosum , representing a new approach for treating pythiosis. 16 …”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of Pythium insidiosum isolates to propolis or geopropolis was determined by measuring the diameter (mm) of radial growth of the colony at 24, 48 and 168 h (7 days) of incubation. All cultures were photographed and the colonies diameter was achieved using the software Image J (image processing and analysis in JAVA; http://rsbweb.nih.gov/ij ), as described by Pires et al 16 Diameters at the angles 0, 45, 90 and 135° of each plate were recorded in mm.…”
Section: Methodsmentioning
confidence: 99%
“…Further clinical evidence is necessary to ascertain these compounds and therapies' true potential and practical applicability in a clinical setting. [33][34][35][36][37][38][39][40][41]…”
Section: Iodidesmentioning
confidence: 99%
“…In recent years, due to its efficiency and low invasive character, antimicrobial photodynamic therapy (aPDT) arises as a promising alternative approach to conventional antifungal medications, which has been demonstrated effective against multiple pathogenic fungi in vitro (Lyon et al, 2013 ; Pires et al, 2013 ; Arboleda et al, 2014 ; Morton et al, 2014 ; Nunes Mario et al, 2014 ; Baltazar et al, 2015 ) and applied successfully in vivo against cutaneous and subcutaneous mycoses (Gilaberte et al, 2011 ; Lyon et al, 2011b ; Souza et al, 2014 ). In addition, aPDT could be a useful approach for the control of biofilms, and has been proposed for the growth control of oral candida (Pereira et al, 2011 ; Pereira Gonzales and Maisch, 2012 ).…”
Section: Introductionmentioning
confidence: 99%